A Retrospective Three-Year Analysis of Adult Scabies at a Tertiary Referral Center in Bali, Indonesia - I Gusti Ayu Agung Praharsini; Luh Putu Sustiana Kartika Sari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Scabies, a parasitic infestation by Sarcoptes scabiei var. hominis, is a global health challenge with significant morbidity, particularly in tropical climates. While often studied in community settings, the profile of adult patients presenting to tertiary care facilities remains under-documented. This study aimed to delineate the clinical-demographic characteristics of adult scabies patients at a major referral hospital in Bali, Indonesia, to better understand this specific patient study. Methods: A retrospective, descriptive study was conducted utilizing electronic medical records from the Dermatology and Venereology outpatient clinic at Prof. Dr. I.G.N.G. Ngoerah General Hospital from January 2021 to December 2023. Following a total sampling method based on strict inclusion and exclusion criteria, data from 38 adult patients with a clinical diagnosis of scabies were extracted. The analysis focused on descriptive statistics to summarize patient demographics, contact history, and prescribed therapeutic regimens. Results: The study of 38 patients had a mean age of 34.1 ± 2.5 years. A male predominance was noted (n=22, 57.9%). The highest frequency of cases was in the 40-49 year age bracket (n=9, 23.7%). Most patients had completed senior high school (n=17, 44.7%) and were employed in the private sector (n=20, 52.6%). A family history of scabies was prevalent (n=18, 47.4%). While indirect transmission via shared clothing was rare (reported by only 7.9%), direct contact through bed sharing with at least one other person was common (n=24, 63.2%). The standard therapeutic protocol was combination therapy, with topical 5% Permethrin and oral antihistamines being the most frequent regimen (n=24, 63.2%). Conclusion: Adult scabies patients at this tertiary center are typically middle-aged, educated, working males. Transmission is overwhelmingly linked to intimate household contact, highlighting the inefficiency of fomite-based spread compared to direct skin-to-skin contact. The standard use of combination therapy reflects a proactive clinical approach to managing both the parasitic infestation and the complex immunologic cascade of pruritus. These findings provide a crucial clinical baseline for this specific patient population.